Impact of technological interventions on productivity of mustard in Kymore Plateau and Satpura hills zone of Madhya Pradesh: IMPACT OF TECHNOLOGICAL INTERVENTIONS ON MUSTARD IN MADHYA PRADESH - JAI SINGH; A K SINGH; A K CHAUBEY; M S BAGHEL (Journal of Oilseeds Research, 2018)
India is the fourth largest oilseed producer in the world. Among the edible oilseed crops cultivated in India, mustard occupies the second position after groundnut with a share of 27.5 per cent in Indian oil economy. It is also one of the important oilseed crops of Madhya Pradesh and is commonly grown in Sidhi district in Kymore Plateau and Satpura Hills zone of the state. Krishi Vigyan Kendra, Sidhi conducted 64 technological frontline demonstrations to know the yield gap between improved package of practices (IP) and farmers practices (FP) under limited irrigation conditions. The study revealed that the mustard yield in improved practice ranged from 8.75 to 13.23 q/ha whereas in farmers practice it was in the range of 6.70 to 10.09 q/ha. The technology demonstration registered highest yield (13.23 q/ha) in 2014-15 which was 31.11 per cent higher over the farmer's practice (10.09 q/ha). Extension gap and technology gap ranged between 1.87 to 3.60 and 2.95 to 11.43 q/ha respectively. The technology index ranged from 19.66 per cent to 57.15 per cent. The technology gap and index reflected farmer's collaboration in carrying out the technology demonstrations with encouraging results in preceding years. The benefit cost ratio was estimated to be 2.15 to 3.64 under demonstration, while it ranged from 1.91 to 2.85 under farmer's practice. The results indicated that these technology frontline demonstrations produced good impact on the farming community regarding the potential of technological interventions in increasing the production of mustard in the target areas.